Macro and micro-circulatory hemodynamics evaluation in sepsis - Figueiredo, Luiz Francisco Poli de; Silva, Eliézer; Corrêa, Thiago Domingos (Revista de Medicina, 2008)
Tissue perfusion evaluation, particularly at the bedside may be very complex inseveral septic patients. Therefore, the evaluation of hemodynamic variables is crucial for an adequate management of those patients. Oxygen delivery and consumption are important variables, but with limited relation to prognosis. In the same direction, lactate levels and mixed or central venous oxygen saturation reflect imbalance between oxygen delivery and consumption. Gastric mucosal PCO2 monitoring and direct visualization of microcirculation may provide a local evaluation of tissue perfusion in shock states with important blood flow heterogeneity.